La responsabilidad social corporativa en modo sistémico: dos modelos alternativos (Estudios) - Raza Mejía, Alejandra Estefanía (2018)
There has been controversy around the idea of social responsibility in the business sector, nevertheless its importance has been rarely acknowledged. The daily economic operations of an organization have negative effects upon its environment that must be dealt with in some way or another; yet, the systemic economic logic of the organization normally defines the ways to cope with social problems in terms of market mechanisms. This article contends that classic and contemporary systems theory offer two different and totally opposed models of social corporative responsibility that can be applied to manage these negative effects.